Implementing Teacher Competency Development Policies to Improve Educational Quality at Muhammadiyah Islamic Elementary School Sidokerto, Plupuh - Isnaini; Siti Halimah; Harun Joko Prayitno; Indri (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the implementation of teacher competency development policies in improving educational quality at Muhammadiyah Islamic Elementary School Sidokerto, Plupuh. The study employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, non-participant observation, and document analysis. The participants included the principal, curriculum coordinator, teachers, administrative staff, and other relevant stakeholders selected through purposive sampling. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings show that teacher competency development was integrated into school planning, academic supervision, teacher meetings, workshops, mentoring, professional working groups, peer discussions, and independent learning. The principal played a central role in identifying teacher needs, determining program priorities, facilitating professional development, providing feedback, and monitoring classroom implementation. These policies contributed to improvements in lesson planning, instructional strategies, digital media use, assessment practices, classroom interaction, professional collaboration, and the integration of Islamic values into learning. Policy implementation was supported by leadership commitment, collegial cooperation, organizational culture, and Muhammadiyah educational values. However, limited funding, high workloads, time constraints, uneven digital competence, and insufficient follow-up reduced the effectiveness of several programs. The study concludes that teacher competency development must be implemented as a continuous institutional cycle consisting of needs assessment, program planning, implementation, mentoring, classroom application, evaluation, and policy improvement. Sustainable policy implementation can strengthen teacher professionalism and gradually improve educational quality.